Avaliação das tecnologias sociais como alternativa de convivência com o Semiárido Cearense: O Projeto de Cisternas - Albuquerque, Cícero Lima (2012)
This study assesses the project selected in Proclamation 02/2008 of the BNB / ETENE - New Social Technologies (ST) Living with the Semi-Arid.These technologies are intended to promote better coexistence with the semiarid, with the increase of farming systems, income generation and community participation. Technology should be used as an example to reapply in the Brazilian semiarid. We opted for an ex post evaluation, which is held throughout the execution or after completion of the project. Through qualitative and quantitative methodologies, we seek to verify the implementation of TS cistern in three communities of the cities of Santana and Acaraú Morrinhos, Ceará. The field was developed with the use of questionnaires with representatives of the families, and interviews with the coordinator and community leaders. We observed the dependency of families on the help of government and civil society, low educational levels of most parents, the small amount of land used for cultivation and production of traditional beans, maize and cassava. We present the characterization of Brazilian Semiarid (SAB), the biome, the coexistence of man with that environment, the technologies adapted to their reality, as well as key programs developed by civil society. Farmers traditionally hold their crops during the winter, receiving little or no technical assistance from municipal and state agencies. The social technology implemented by the project requires more time for use to generate satisfactory income families. Water is a precious asset for these communities, however, it is essential that the availability of infrastructure such as better roads, schools and health posts to local development and improved coexistence with the semiarid.